Ultraviolet radiation exposure triggers neurokinin-1 receptor upregulation in ocular tissues in vivo. (September 2018) - Gross, Janine; Wegener, Alfred R.; Kronschläger, Martin; Holz, Frank G.; Schönfeld, Carl-Ludwig; Meyer, Linda M.
Abstract: The purpose of this study was to investigate the neurokinin receptor-1 (NKR-1) protein expression in ocular tissues before and after supra-cataract threshold ultraviolet radiation (UVR-B peak at 312 nm) exposure in vivo in a mouse model. Six-week-old C57Bl/6 mice were unilaterally exposed to a single (2.9 kJ/m 2 ) and an above 3-fold UVR-B cataract threshold dose (9.4 kJ/m 2 ) of UVR. UVR-exposure (λpeak = 312 nm) was performed in mydriasis using a Bio-Spectra exposure system. After latency periods of 3 and 7 days, eyes were fixed in 4% paraformaldehyde, embedded in paraffin, sectioned and stained with fluorescence coupled antibody for NKR-1 and DAPI for cell nuclei staining. Control animals received only anesthesia but no UVR-exposure. Cataract development was documented with a Leica dark-field microscope and quantified as integrated optical density (IOD). NKR-1 is ubiquitously present in ocular tissues. An above 3-fold cataract threshold dose of UV-radiation induced NKR-1 upregulation after days 3 and 7 in the epithelium and endothelium of the cornea, the endothelial cells of the iris vessels, the pigmented epithelium/stroma of the ciliary body, the lens epithelium, pronounced in the nuclear bow region and the inner plexiform layer of the retina. A significant upregulation of NKR-1 could not be provoked with a single cataract threshold dose (2.9 kJ/m 2 UVR-B) ultraviolet irradiation. All exposed eyes developed anterior subcapsular cataracts. Neurokinin-1 receptor is present ubiquitously in ocular tissues including the lens epithelium and the nuclear bow region of the lens. UV-radiation exposure to an above 3-fold UVR-B cataract threshold dose triggers NKR-1 upregulation in the eye in vivo . The involvement of inflammation in ultraviolet radiation induced cataract and the role of neuroinflammatory peptides such as substance P and its receptor, NKR-1, might have been underestimated to date. Highlights: We investigate neurokinin-1 receptor expression in ocular tissues after in vivo unilateral ultraviolet radiation exposure. We demonstrate for the first time that the neurokinin-1 receptor is present in the lens. UVR triggers an upregulation of neurokinin-1 receptor in vivo in different ocular tissues including the lens. The role of inflammation in UVR cataract has been underestimated so far.